Transforming Ethiopian agriculture: Validating and scaling site-specific fertilizer recommendations to 72,000+ farmers via digital advisory. - Desta, Lulseged Tamene; Mesfin, Tewodros; Abera, Wuletawu; Degefie, Tibebe; Ebrahim, Mohammed; Tilaye, Asmalu; Chernet, Meklit Tariku; Merga, Feyera; Desalegn, Temesgen; Yitaferu, Birru Woldetsadik (2025)
The independent validation of the NextGen Decision Support Tool (DST)-based advisory by Ethiopia's national research system highlights its superior performance and marks a pivotal step in integrating site-specific, digital fertilizer recommendations into the national extension framework. This advisory has boosted wheat yield by 14% to 20% and increased net returns by up to $665 per hectare. With demonstrated impact and scalability, reaching over 72,000 farmers, the DST is improving productivity, sustainability, and livelihoods, solidifying its position as a transformative asset for Ethiopian agriculture.